Co-production strategy, retail competition, and market segmentation. Issue 2 (7th November 2019) - Wang, Junbin; Fan, Xiaojun
Abstract : Purpose: The purpose of this paper is to examine the effect of manufacturers' co-production strategy on market segmentation and channel performance under retail competition. Design/methodology/approach: It differs from previous empirical studies by primarily focusing on the increment in consumer value accompanying co-production. The authors establish a game-theoretical model to analyze the impact of co-production on market segmentation and the profitability of channel members in a competitive retail environment. Findings: The results reveal that manufacturers introducing co-production expand market coverage and benefit all channel members, when the intensity of competition is sufficiently high, especially for retailers with low-quality levels, who are out of the market without co-production. Furthermore, with the increase in customer valuation through co-production, employing a co-production strategy is always a dominant strategy for manufacturers. Research limitations/implications: First, although the authors assume a monopoly manufacturer and two duopoly retailers, adding competition between manufacturers should enrich the model. Multiple products with vertical or horizontal differentiation could also be introduced into the model. Second, the authors use the multiplicative utility function to model the value co-creation effect on consumers; however, different utility functions may yield significantly different results and implications. Third, the authors model a one-shot game in a single product selling period; future studies may employ multi-period games to obtain further insight into co-production strategy. Finally, the model assumes that all consumers are homogenous in the extent of value creation and hassle cost. Future research may find it interesting to consider heterogeneity in these characteristics. Practical implications: The business world today already sees the power of leadership in a supply chain to have shifted from manufacturers to retail giants such as Walmart, Home Depot and Best Buy. The findings also propose a new route to counteract the emergence and rise of dominant retailers. On the other hand, with the application of new technology in the retail industry such as 3D avatar, AR/VR, Internet of Things, consumers are more likely to participate in various forms of co-production activities, how to execute the co-production strategy has become more and more important for managers. Social implications: The conclusion of this study points out the way to achieve a win–win outcome under which both channel members including manufacturer and retailers and consumers can be better off, that is, the channel can reach Pareto improvement, so the social welfare is increased accordingly. Originality/value: The authors propose an analytical framework to examine the effects of co-production and competition on market segmentation and profitability, and prove that co-production is a powerful marketing tool that can attract consumers and increase profitability, which manufacturers can incorporate into their products even in a competitive environment.